2019
DOI: 10.1186/s13014-019-1437-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between the location of transposed ovary and ovarian dose in patients with cervical cancer treated with postoperative pelvic radiotherapy

Abstract: Background and purposeHow to protect the ovarian function during radiotherapy is uncertain. The purpose of this study was to explore the association between the location of the transposed ovary and the ovarian dose in patients with cervical cancer received radical hysterectomy, ovarian transposition, and postoperative pelvic radiotherapy.MethodsA retrospective analysis was conducted of 150 young patients with cervical cancer who received radical hysterectomy, intraoperative ovarian transposition, and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
1
21
0
4
Order By: Relevance
“…Over the past 30 years, ovarian insufficiency after OT has varied from 33% to 100% in different comparisons (20). Consistent with the previous study results (20), our current study found that 68.8% (22/32) of OT patients retained ovarian function almost 1 year after radiation therapy, which is slightly higher than the results (41/105, 39.0%) of Yin et al (14), but slightly lower than the results (56/77, 72.7%) of Lv et al (15). No ovarian metastasis or recurrence was observed in any of the 51 cases.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Over the past 30 years, ovarian insufficiency after OT has varied from 33% to 100% in different comparisons (20). Consistent with the previous study results (20), our current study found that 68.8% (22/32) of OT patients retained ovarian function almost 1 year after radiation therapy, which is slightly higher than the results (41/105, 39.0%) of Yin et al (14), but slightly lower than the results (56/77, 72.7%) of Lv et al (15). No ovarian metastasis or recurrence was observed in any of the 51 cases.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Pahisa et al (23) and Han et al (12) investigated the application of OT in patients with cervical cancer undergoing radiation therapy (4 fields, whole pelvis radiation) and found no cases of ovarian metastasis. Yin et al and Lv et al (14,15) also reported no ovarian metastasis in any OT cases during the follow-up period after postoperative IMRT radiation. Soda et al noted that the actual rate of these OT ovarian recurrences is rare after patients undergo postoperative radiation (24).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…25 Transposition 1.1-1.5cm above the iliac crest is associated with increased likelihood of normal ovarian function after EBRT. 26,27 Ongoing clinical studies…”
Section: Ovarian Transpositionmentioning
confidence: 99%
“…Транспозиция яичников представляет собой хирургическое изменение положения яичников таким образом, чтобы они находились вне поля облучения во время лучевой терапии. Впервые данная операция была предложена в 1958 г. именно для больных раком шейки матки перед планируемой лучевой терапией [11]. Для осуществления транспозиции пересекается собственная связка яичника (почти всегда еще и маточная труба), после чего яичник на сосудисто-нервной ножке, находящейся в воронко-тазовой связке, фиксируется в латеральном канале брюшной полости, перед большой поясничной мышцей, или высоко спереди и латерально [12].…”
Section: транспозиция яичников и альтернативные методикиunclassified